ENERGY ABSORPTION PROPERTIES OF AXIALLY LOADED METAL CIRCULAR TUBE UNDER IMPACT LOAD - HONG Xiang; YAO Song; GUO XingXing (Jixie qiangdu)
In order to study the mechanical behavior and energy absorption characteristics of a metal circular tube with axial pre-compression under axial impact load. The finite element analysis was carried out based on Abaqus. A circular tube whoseR/t value is 15 was studied. At the same time,considering the influence of the initial geometric imperfections,the initial geometric deformation caused by pre-loading and boundary conditions,the corresponding control group was established in the finite element simulation. The simulation results are concluded as follows:（ 1） The deformation mode of the fixed end simply supported is more complex than the clamped case. Energy absorption characteristics and the corresponding deformation modes have a great relationship. When the asymmetric fold is more,the energy absorption characteristic becomes worse.（ 2） Initial geometric imperfections can induce circular tubes to produce non-axisymmetric folds,while the axial pre-compression tube is less sensitive to initial geometric imperfections,and the smaller pre-loading can counteract the effects of initial geometric imperfections.